Designing Inventory Information Sytem of Finished Goods for Varia Usaha Beton, Co. Ltd - Emmy Wahyuningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
Nowadays, the web-based information system is widely used in various fields, including at PT. Varia Usaha BetonGresik. Data Collection Inventory of finished goods needs to be done in order to know the residual of pre-printedconcrete sold and guarantee the smooth flow of goods. Therefore, it is necessary to record all revenue received fromthe realization of production (input) and delivery realization (output). The data recording aims to be easily identifiedby the overloaded goods and the goods that must be reproduced because of stockout, and to integrate data amongthe general affairs division, production division, PPIC (Production Planning Inventory Control) division to supportthe delivery process.